2022
DOI: 10.1159/000524216
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenetic Heterochrony in Chick, Lizard, and Rat Mapped with Wholemount Acetylcholinesterase and the Prosomeric Model

Abstract: In the developing brain, the phenomenon of neurogenesis is manifested heterotopically, that is, much the same neurogenetic steps occur at different places with a different timetable. This is due apparently to early molecular regionalization of the neural tube wall in the anteroposterior and dorsoventral dimensions, in a checkerboard pattern of more or less deformed quadrangular histogenetic areas. Their respective fate is apparently specified by a locally specific combination of active/repressed genes known as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 95 publications
(152 reference statements)
1
16
0
Order By: Relevance
“…Interpreting their data in terms of the columnar model, Aslanpour et al (2020b) identified a "rostrocaudal" gradient in VMH birthdates, which we translate topologically to the prosomeric model as a dorsoventral gradient. Presumably TuD neurogenesis precedes that of TuI, which is consistent with reported wholemount rat results using AChE as an early differentiation marker (Puelles et al 2015;Amat et al 2022). Accordingly, we deduce that our dorsal tuberal Nr5a1 and Nkx2.2 VMH cells would be born earlier (E10.5) than the ventral ones (E11.5), due to their origin in the more precocious TuD area.…”
Section: Both Tui and Tud Are Progenitor Areas For Vmh Cellssupporting
confidence: 90%
See 2 more Smart Citations
“…Interpreting their data in terms of the columnar model, Aslanpour et al (2020b) identified a "rostrocaudal" gradient in VMH birthdates, which we translate topologically to the prosomeric model as a dorsoventral gradient. Presumably TuD neurogenesis precedes that of TuI, which is consistent with reported wholemount rat results using AChE as an early differentiation marker (Puelles et al 2015;Amat et al 2022). Accordingly, we deduce that our dorsal tuberal Nr5a1 and Nkx2.2 VMH cells would be born earlier (E10.5) than the ventral ones (E11.5), due to their origin in the more precocious TuD area.…”
Section: Both Tui and Tud Are Progenitor Areas For Vmh Cellssupporting
confidence: 90%
“…The prosomeric hypothalamus consists of two prosomeres, hp2 and hp1, which represent its structure transversal to the axis of the forebrain (Fig. 1 ; the prosomeric axis is co-defined by the notochord, the floorplate, the alar-basal boundary and the roofplate as mutually parallel longitudinal reference landmarks lying at different dorsoventral levels; Puelles 2018 ; Amat et al 2022 ; the optic tract may be taken as another such reference; Puelles 2022 ). These two units are both hypothalamo-telencephalic in spatial range and contain respectively the terminal hypothalamus which extends into the non-evaginated preoptic telencephalic subpallium (THy in hp2; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LH2 is the LH subregion associated with the periretromamillary (PRM) basal subdomain. This subdomain was first defined molecularly by Puelles et al [ 17 ] as associated with selective Otp and Sim1 basal plate signals, unrelated to alar expression domains of the same markers (see also [ 82 – 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a descriptive tour de force, Amat et al [2022] present a comprehensive analysis of neurogenic trajectories in amniotes by examining histological samples of developing brains of lizards, chickens, and rats. By adopting a neuromeric framework of brain organization, wholemount acetylcholinesterase preparations -used as a marker of postmitotic neurons -are thoroughly examined between species and stages with a focus on the relative positions, trajectories, and functional boundaries along the rostro-caudal and basal-to-alar axes.…”
mentioning
confidence: 99%